The Effect of Mobile Learning Benefits Perception in Supporting Entrepreneurship Apprenticeships Program on Students Entrepreneurship Intention - ., Hendrajaya (KnE Social Sciences, 2018)
In the Information Technology and Internet Era, Mobile Learning has the potential to support Entrepreneurship Education in Apprenticeship Program. This study aims to test and analysis effect of Mobile Learning Benefits Perception in Supporting Entrepreneurship Education in Apprenticeship Program on Students Entrepreneurship Intention. The study was conducted by a survey of 140 Final Students at the College of Economics of Tourism in Semarang City who is or has been apprenticed. The benefits of Mobile Learning are measured by students’ perceptions of acquiring knowledge, experience and social motivation towards entrepreneurship. The analysis was done by using Structural Equation Modeling (SEM). The result of this research generally finds that entrepreneurship learning through the apprenticeship program and Perception of M-Learning Benefit significantly influence entrepreneur intention either directly or through perceived feasibility and perceived desirability. The total effect of entrepreneurship education in the apprenticeship program has greater path coefficient compared to M-Learning benefit perception, so where M-Learning is only as a supporter of entrepreneurship education in apprenticeship program in increasing students entrepreneurship intention. The results of the study provide the implications of the development of electronic learning through M-Learning in support of entrepreneurial learning. M-Learning, for example, provides independent learning potential, knowledge sharing opportunities, experience sharing, problemsolving based and entrepreneurial motivation facilitate. overcome the problem of busy mentor time in the industrial environment. The results of the study provide implications for the development of M-Learning in supporting entrepreneurial learning such as through curriculum development and learning design. Keywords: Student Entrepreneurship Intention, Apprenticeships, Mobile Learning